Catastrophic health expenditure: a comparative study between hypertensive patients with and without complication in rural Shandong, China - Xinyi Zhang; Qiongqiong Xu; Xiaolei Guo; Zhengyue Jing; Long Sun; Jiajia Li; Chengchao Zhou (BMC, 2020)
Abstract Background Some previous studies have assessed catastrophic health expenditure (CHE) in households with hypertensive patients, but few have examined the difference of CHE in hypertensive patients with and without complications. The purpose of this study is to compare the incidence and determinants of CHE between hypertensive patients with and without complications. Methods Data of this study were from a cross-sectional study in Shandong Province in China in 2016. Of the recruited 3457 hypertensive patients registered in the NCDs management system in the sampling villages, 3113 completed the survey, with a response rate of 90.05%.CHE was defined as out-of-pocket payments for hypertensive care that equaled or exceeded 40% of the household capacity to pay (non-food expenditure). Hypertension complications (e.g., stroke, coronary heart disease, hypertensive kidney disease, etc.) were collected in this study, which was categorized into 0 (no), 1(single), and 2 and more according to the types of hypertensive complications. We employed Chi-square test to explore associated factors and logistic regression model to identify the determinants of CHE. Results The incidence of CHE and impoverishment is 13.6 and 10.8% among hypertensive patients. The incidence of CHE with one complication is 25.3% (Ρ = 0.000, OR = 2.29) and 47.3% (P = 0.000, OR = 3.60) in patients with two or more complications, which are both statistically higher than that in patients without complication (6.1%). Across all types of patients, income levels are inversely related to the incidence of CHE. Patients who use outpatient or inpatient service are more likely to experience CHE (Ρ = 0.000). Factors including living arrangements, family size, educational attainment are found to be significantly associated with CHE in some subgroups (Ρ <0.05). Conclusions CHE and impoverishment incidence among hypertensive patients are both high in rural China. Patients with hypertensive complication are at higher catastrophic risk than those without complication. More attention needs to be paid to households with hypertension patients, especially for those with hypertension complications.